Temporal analysis of losing possession of the ball leading to conceding a goal: A study of the incidence of perturbation in soccer - Shafizadeh, M.; Lago-Penas, C.; Gridley, A.; Platt, G. K. (International Journal of Sports Science and Coaching, 2014)
The aim of this study was to examine the temporal occurrence of losing possession of the ball in soccer and its association with conceding a goal. Thirty two senior national teams competing in the 2010 World-Cup in South Africa and twelve youth soccer clubs were selected for match analysis. The results of time distribution analysis showed a significant positive skewness (K-SZ =3, S=0.463, p=0.000) for losing possession of the ball, transition time in senior (K-SZ =1.82, S=1.57, p=0.003) and youth groups (K-SZ =2.85, S=1.29, p=0.002) and normal distribution for variability of time to losing the ball (K-SZ =1.07, S= -0.280, p=0.19). The results of an independent t test showed that there was a significant difference (t=2.71, p=0.008) in transition time between youth and senior groups. In conclusion, this study showed that the number of times that the ball was lost increased near to a goal being conceded and the duration of the most recent loss was very close to goal-conceding. Thus effective strategies that have been employed to destabilise opponents include increasing the number of perturbations through losing possession of the ball, speeding up the transition periods and the final strike after the opponents lose the ball.